Molecular Cloning and Expression Characteristics of otx2 and eya1 During the Early Development of Seriola aureovittata - Yan JIANG; Xin LIU; Yongjiang XU; Aijun CUI; Bin WANG; Xinfu LIU; Xuezhou LIU; Zhiyong XUE (Progress in Fishery Sciences)
Yellowtail kingfish (Seriola aureovittata) is a pelagic migratory fish species with a global distribution. In recent years, interest in the aquaculture of this species has increased worldwide because of its high flesh quality and fast growth. As a large and fast-swimming pelagic fish, yellowtail kingfish has good adaptability to land-based industrial recirculating and offshore net cage modes. With the development of aquaculture technology, more attention has been paid to animal behavior research, which will promote the welfare level in aquaculture. Light, sound, temperature, density, and flow velocity are important factors affecting the welfare of farmed fish. The development, morphological structure, and regulatory mechanism of sensory organs, including visual, gustatory, olfactory, and auditory organs, are becoming increasingly important in the study of animal behavior.Orthodenticle homeobox 2 (OTX2) and eye absent 1 (EYA1) play important roles in regulating the ontogeny, differentiation, and development of visual, gustatory, olfactory, and auditory organs. In order to study the expression characteristics of otx2 and eya1 in yellowtail kingfish during early development, otx2 and eya1 were identified from brain tissue with specific kits. The lengths of otx2 and eya1 open reading frame domain were 876 and 1, 962 bp encoding 291 and 653 amino acids, respectively. Among these, OTX2 consists of a homologous domain from the 42nd to 93rd amino acids and a TF-Otx domain containing 82 amino acids; the C-terminal of EYA1 is an EYA domain encoding 246 amino acids. These two genes had a wide range of tissue expression characteristics, including in eye, brain, pituitary, head kidney, heart, liver, spleen, kidney, mid-gut, and ovary tissues. The highest expression level of otx2 was obtained in eye tissues followed by brain tissues, and the values in these two tissues were significantly higher than those in other tissues (P < 0.05). The highest expression level of eya1 was obtained in pituitary tissues followed by ovary tissues, and the values in these two tissues were significantly higher than those in other tissues (P < 0.05). During embryonic development, expression of otx2 and eya1 could be detected at each stage, and levels were upregulated at a late stage, during which otx2 and eya1 reached peak values at hatching stage and when the embryo encircled 4/5 of the yolk sac, respectively. At the larval and juvenile stages, the expression of otx2 and eya1 could be detected, with high expression levels at the early stage, during which the expression level of otx2 was first upregulated and then downregulated; the expression level at 3–25 dph (days post-hatching) was significantly higher than those at 1 dph and 30–60 dph, with the highest level reached at 20 dph (P < 0.05). The expression of eya1 showed a downward trend, with the highest level reached at 1 dph (P < 0.05); the expression levels at 30–60 dph were significantly lower than those at 7–25 dph (P < 0.05). This study provides a molecular basis for understanding the physiological functions of otx2 and eya1 during the development of sensory organs and the regulatory mechanisms in yellowtail kingfish.